Designing Tangible User Interfaces for NFC Phones. (23rd January 2012) - Pyykkönen, Mikko; Riekki, Jukka; Alakärppä, Ismo; Sanchez, Ivan; Cortes, Marta; Saukkonen, Sonja
Abstract : The increasing amount of NFC phones is attracting application developers to utilize NFC functionality. We can hence soon expect a large amount of mobile applications that users command by touching NFC tags in their environment with their NFC phones. The communication technology and the data formats have been standardized by the NFC Forum, but there are no conventions for advertising to the users NFC tags and the functionality touching the tags triggers. Only individual graphical symbols have been suggested when guidelines for advertising a rich variety of functionality are called for. In this paper, we identify the main challenges and present our proposal, a set of design guidelines based on more than twenty application prototypes we have built. We hope to initiate discussion and research resulting in uniform user interfaces for NFC-based services.